A chalcone showing positional disorder, two related diarylcyclohexenones showing enantiomeric disorder and a related hydroxyterphenyl, all derived from simple carbonyl precursors. Issue 7 (26th June 2015) - Salian, Vinutha V.; Narayana, Badiadka; Yathirajan, Hemmige S.; Akkurt, Mehmet; Çelik, Ömer; Ersanlı, Cem Cüneyt; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> Four compounds are reported, all of which lie along a versatile reaction pathway which leads from simple carbonyl compounds to terphenyls. (2E)‐1‐(2, 4‐Dichlorophenyl)‐3‐ [4‐(prop‐1‐en‐2‐yl)phenyl]prop‐2‐en‐1‐one, C18H14Cl2O, (I), prepared from 4‐(prop‐1‐en‐2‐yl)benzaldehyde and 2, 4‐dichloroacetophenone, exhibits disorder over two sets of atomic sites having occupancies of 0.664 (6) and 0.336 (6). The related chalcone (2E)‐3‐(4‐chlorophenyl)‐1‐(4‐fluorophenyl)prop‐2‐en‐1‐one reacts with acetone to produce (5RS)‐3‐(4‐chlorophenyl)‐5‐[4‐(propan‐2‐yl)phenyl]cyclohex‐2‐en‐1‐one, C21H21ClO, (II), which exhibits enantiomeric disorder with occupancies at the reference site of 0.662 (4) and 0.338 (4) for the (5R) and (5S) forms; the same chalcone reacts with methyl 3‐oxobutanoate to give methyl (1RS, 6SR)‐4‐(4‐chlorophenyl)‐6‐[4‐(propan‐2‐yl)phenyl]‐2‐oxocyclohex‐3‐ene‐1‐carboxylate, C23H23ClO3, (III), where the reference site contains both (1R, 6S) and (1S, 6R) forms with occupancies of 0.923 (3) and 0.077 (3), respectively. Oxidation, using 2, 3‐dichloro‐5, 6‐dicyano‐1, 4‐benzoquinone, of ethyl (1RS, 6SR)‐6‐(4‐bromophenyl)‐4‐(4‐fluorophenyl)‐2‐oxocyclohex‐3‐ene‐1‐carboxylate, prepared in a similar manner to (II) and (III), produces ethyl 4′′‐bromo‐4‐fluoro‐5′‐hydroxy‐1, 1′:3′, 1′′‐terphenyl‐4′‐carboxylate, C21H16BrFO3, (IV), which crystallizes with Z′ = 2 in the space group P<inline-graphic xlink:href="ark:/27927/pgj1m92t9sb" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. There are no significant intermolecular interactions in the structures of compounds (I) and (II), but for the major disorder component of compound (III), the molecules are linked into sheets by a combination of C—H...O and C—H...π(arene) hydrogen bonds. The two independent molecules of compound (IV) form two different centrosymmetric dimers, one built from inversion‐related pairs of C—H...O hydrogen bonds and the other from inversion‐related pairs of C—H...π(arene) hydrogen bonds. Comparisons are made with related compounds.